Selection of informative acoustic emission parameters for determining the wear rate of woodworking equipment in transient modes - Voitov, A.V.; D’yakonov, V.I.; Gradiskiy, Y.O. (Problems of Tribology, 2025)
The directions of application of the acoustic emission method for the study of transient processes in tribosystems are considered. woodworking equipment during running-in. The use of this method will allow obtaining information about the condition of friction surfaces and the wear rate during transient processes (running-in) in online mode. To justify choice informative AE parameters analyzed the type of AE - signal frames captured during the transition process at characteristic points. It is shown that when evaluating speed wear in transient modes is best use acoustic emission power radiation. After completion transitional process (steady state of operation), the AE signal frame takes the form that much different from transitional regime. Experimental research presented in the form of experimental dependencies thats reflect average value power of AE signals. Along the axis Y postponed relevant calculated value speed works dissipation in tribosystems , unit measurement - J/s. Received dependencies allow determine speed works dissipation in tribosystems woodworking equipment during the transition process by values power signals acoustic emissions, which allowed us to develop a calculation methodology quantities speed wear in woodworking equipment during training in any point transitional process.